Use of GIS technology in the training of future engineers - Грищенко, Світлана (Pedagogy of Higher and Secondary Education, 2014)
Gryschenko S. N. Use of GIS technology in the training of future engineers. The article describes the features of the use of geographic information technologies in preparation for future engineers. The notions of «information and communication technologies», «GIS technology». Displayed posledzhovatelnost actions of their application in practice, found advantages and disadvantages in the educational process.